Reassortant Group A Rotavirus from Straw-colored Fruit Bat ( Eidolon helvum ) - Esona, Mathew D.; Mijatovic-Rustempasic, Slavica; Conrardy, Christina; Tong, Suxiang; Kuzmin, Ivan V.; Agwanda, Bernard; Breiman, Robert F.; Banyai, Krisztian; Niezgoda, Michael; Rupprecht, Charles E.; Gentsch, Jon R.; Bowen, Michael D. (Emerging infectious diseases, 2010)
Bats are known reservoirs of viral zoonoses. We report genetic characterization of a bat rotavirus (Bat/KE4852/07) detected in the feces of a straw-colored fruit bat (Eidolon helvum). Six bat rotavirus genes (viral protein [VP] 2, VP6, VP7, nonstructural protein [NSP] 2, NSP3, and NSP5) shared ancestry with other mammalian rotaviruses but were distantly related. The VP4 gene was nearly identical to that of human P[6] rotavirus strains, and the NSP4 gene was closely related to those of previously described mammalian rotaviruses, including human strains. Analysis of partial sequence of the VP1 gene indicated that it was distinct from cognate genes of other rotaviruses. No sequences were obtained for the VP3 and NSP1 genes of the bat rotavirus. This rotavirus was designated G25-P[6]-I15-R8(provisional)-C8-Mx-Ax-N8-T11-E2-H10. Results suggest that several reassortment events have occurred between human, animal, and bat rotaviruses. Several additional rotavirus strains were detected in bats.